2021
DOI: 10.1158/1538-7445.am2021-1014
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1014: Repurposing the anti-rheumatic gold compound auranofin for high-grade serous ovarian cancer therapy

Abstract: Auranofin (AF) is a gold compound approved in 1985 as a main treatment against rheumatoid arthritis. However, as new anti-rheumatoid agents displaced the use of AF, there have been studies aiming to repurpose the drug to treat other diseases, including cancer. In this study, we investigated the potentiality of AF to impair the growth of high-grade serous ovarian cancer (HGSOC) cells regardless of platinum (CDDP) sensitivity. Preliminary studies utilizing a colorimetric proliferation assay revealed that HGSOC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There is already clinical evidence that VEGF secreted by melanoma cells could recruit MSDCs and Tregs to TME for suppressing the effector function of CTLs, thus contributing to their immune escape. Interestingly, recent reports reveal that AUR could demonstrate potent VEGF suppressing capability through inhibiting ERK1/2-HIF-1α signaling activity in tumor cells [53][54][55] . Indeed, we have carried out transcriptome sequencing on AUR-treated B16F10 cells to screen the treatment-induced impact on various immune-related signaling pathways, and the KEGG enrichment analysis results immediately suggested that AUR treatment pronouncedly inhibited the VEGF signaling pathways (Fig.…”
Section: The Crosstalk Between Tumor Cells and Immunosuppressive Cell...mentioning
confidence: 99%
“…There is already clinical evidence that VEGF secreted by melanoma cells could recruit MSDCs and Tregs to TME for suppressing the effector function of CTLs, thus contributing to their immune escape. Interestingly, recent reports reveal that AUR could demonstrate potent VEGF suppressing capability through inhibiting ERK1/2-HIF-1α signaling activity in tumor cells [53][54][55] . Indeed, we have carried out transcriptome sequencing on AUR-treated B16F10 cells to screen the treatment-induced impact on various immune-related signaling pathways, and the KEGG enrichment analysis results immediately suggested that AUR treatment pronouncedly inhibited the VEGF signaling pathways (Fig.…”
Section: The Crosstalk Between Tumor Cells and Immunosuppressive Cell...mentioning
confidence: 99%
“…Among the various compounds known to inhibit the TXN system, auranofin (AUR) is the only clinically available drug. Primarily approved for rheumatoid arthritis, AUR has displayed remarkable antitumor characteristics and is now extensively tested as a putative antitumor agent in preclinical and clinical studies (NCT01737502) 13,14 . Although alternative molecular targets have been associated with the anticancer effects of AUR, 15,16 it is widely believed that TXN‐R is the primary target at the low micromolar concentration range 17–19 .…”
Section: Introductionmentioning
confidence: 99%
“…Primarily approved for rheumatoid arthritis, AUR has displayed remarkable antitumor characteristics and is now extensively tested as a putative antitumor agent in preclinical and clinical studies (NCT01737502). 13 , 14 Although alternative molecular targets have been associated with the anticancer effects of AUR, 15 , 16 it is widely believed that TXN‐R is the primary target at the low micromolar concentration range. 17 , 18 , 19 Notably, AUR showed promising antitumor effects in various B‐cell malignancies, 11 , 12 including B‐ALL.…”
Section: Introductionmentioning
confidence: 99%